1997
DOI: 10.1073/pnas.94.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of nuclear DNA to triplex-forming oligonucleotides: The integrated HIV-1 provirus as a target

Abstract: The control of gene transcription by antigene oligonucleotides rests upon the specific recognition of doublehelical DNA by triplex-forming oligonucleotides. The development of the antigene strategy requires access to the targeted DNA sequence within the chromatin structure of the cell nucleus. In this sudy we have used HIV-1 chronically infected cells containing the HIV provirus as endogenous genes to demonstrate that the integrated HIV-1 proviral genome is accessible to triplex-forming oligonucleotides within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 51 publications
5
120
0
Order By: Relevance
“…Among these are chemical modifications that result in neutral or cationic backbones to reduce the electrostatic repulsion between the negatively charged phosphodiester backbone of the TFO with that of the target DNA duplex. Examples of such modifications include thioate linkages [56,57], N 3' − P 5' phosphoramidates [58,59], and morpholino phosphoramidate linkages [60]. The cationic phosphoramidate linkages, N,Ndiethylethylenediamine and N,N-dimethylaminopropylamine, confer increases in TFO binding affinity and intracellular activity [61].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…Among these are chemical modifications that result in neutral or cationic backbones to reduce the electrostatic repulsion between the negatively charged phosphodiester backbone of the TFO with that of the target DNA duplex. Examples of such modifications include thioate linkages [56,57], N 3' − P 5' phosphoramidates [58,59], and morpholino phosphoramidate linkages [60]. The cationic phosphoramidate linkages, N,Ndiethylethylenediamine and N,N-dimethylaminopropylamine, confer increases in TFO binding affinity and intracellular activity [61].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…1B) [10,11]. Triplex-forming oligonucleotides (TFOs) can interfere with the binding of proteins [12] and affect the transcription of a specific gene [13]. At least three classes of triplexes exist which differ in sequence composition and relative orientations of the phosphodiester backbone of the third strand [14].…”
Section: Fig 1 (A) Formulae Of Cryptolepine (5-methyl Indolo[23b]-mentioning
confidence: 99%
“…When the target sequence was located in transcription region, the triplex formation efficiency varied from one gene to another and was not correlated with the status of gene expression. However, different degrees of triplex formation were observed when HIV-1 genome was integrated into different sites of the host genome (396). Since transcriptional activation can change chromatin organization including nucleosome disruption or displacement in several systems (399,400), the transcription status of target DNA sequences must affect the triplex formation efficiency.…”
Section: 33mentioning
confidence: 99%
“…The accessibility is dependent on the sites of target sequences and TFOs used. In a pioneer study, Giovannangeli et al demonstrated triplex formation of psoralen modified 15-mer PO-or PN-TFOs with genomic DNA within permeabilized cells chronically infected with viral HIV-1 (396). PN-TFO showed higher efficiency in triplex formation than PO analogue.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation